2011
DOI: 10.1097/eja.0b013e32833fad52
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrical nerve stimulation on ST36 and SP6 acupoints prevents hyperglycaemic response during anaesthesia: a randomised controlled trial

Abstract: We found TENS at bilateral ST36 and SP6 acupoints to be an alternative means of managing the plasma glucose level and improving insulin resistance perioperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…An earlier study showed that the application of TENS to the ST36 and SP6 acupoints can prevent hyperglycemic responses during anesthesia. Researchers found that TENS can significantly decrease plasma glucose levels, insulin levels, and the HOMA index in the experimental group compared with the placebo group after the use of TENS during preoperative elective hysterectomy [13]. Thus, TENS may be considered a new treatment modality for plasma glucose control and insulin activity enhancement before surgery.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study showed that the application of TENS to the ST36 and SP6 acupoints can prevent hyperglycemic responses during anesthesia. Researchers found that TENS can significantly decrease plasma glucose levels, insulin levels, and the HOMA index in the experimental group compared with the placebo group after the use of TENS during preoperative elective hysterectomy [13]. Thus, TENS may be considered a new treatment modality for plasma glucose control and insulin activity enhancement before surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture may alleviate the stress response by balancing the sympathetic tone. EA at ST36 and SP6 for 30 min before induction prevented hyperglycaemia during anaesthesia, 52 and the increased levels of cortisone and increased sensitivity to insulin were attenuated. 48 52 Patients with some refractory complications may choose acupuncture as a potentially effective and non-invasive therapy.…”
Section: Other Complicationsmentioning
confidence: 90%
“…In another recent RCT, the effect of transcutaneous electrical nerve stimulation (TENS) on acupuncture points on serum glucose, serum insulin, and insulin resistance during surgical anesthesia for elective hysterectomy was measured in 60 women without diabetes [55]. In this study, participants were randomized to either TENS treatment that received 30 min of electrical stimulation or placebo, in which the electrical contact pads were placed on the points but were not stimulated electrically.…”
Section: Acupuncture and Related Therapiesmentioning
confidence: 99%